Pengembangan Profesionalisme Guru Melalui Pelatihan dan Pendampingan Penulisan Karya Ilmiah bagi Guru Sekolah Dasar Negeri - Sobri, Ahmad Yusuf; Juharyanto, Juharyanto; Prestiadi, Dedi; 'Ilmi, Achmad Miftachul (Universitas Negeri Malang, 2023)
This service aims to develop the professionalism of elementary school teachers through training and mentoring in scientific writing. The activity was carried out in the KKG Gugus 7, Blimbing District, Malang City, involving 48 teachers as participants. The implementation method was carried out in stages of preparation, socialization, implementation, and evaluation. The results of this service activity were that 25 teachers were able to submit scientific articles to Sinta-indexed national journals and 10 teachers chose to submit their scientific articles to non-Sinta indexed national journals. In addition, there were still 13 teachers who needed revisions to their scientific papers in order to be eligible for submission to Sinta-indexed national journals. Based on the results of the activity, it can be concluded that training and mentoring in scientific writing can be an effective strategy in developing the professionalism of elementary school teachers. Therefore, it is recommended that similar activities be carried out regularly to support the development of teacher professionalism in the field of scientific writing. Pengabdian ini bertujuan untuk mengembangkan profesionalisme guru SD melalui pelatihan dan pendampingan penulisan karya ilmiah. Kegiatan dilaksanakan pada KKG Gugus 7 Kecamatan Blimbing Kota Malang dengan melibatkan 48 guru sebagai peserta. Metode pelaksanaan kegiatan dilakukan dengan tahapan persiapan, sosialisasi, implementasi, dan evaluasi. Hasil dari kegiatan pengabdian ini adalah sebanyak 25 guru yang berhasil melakukan submit artikel ilmiah pada jurnal nasional terindeks Sinta dan 10 guru memilih untuk submit artikel ilmiahnya pada jurnal nasional tidak terindeks. Selain itu, masih terdapat 13 guru yang memerlukan revisi pada karya ilmiahnya agar layak untuk disubmit pada jurnal nasional terindeks. Berdasarkan hasil kegiatan, dapat disimpulkan bahwa pelatihan dan pendampingan penulisan karya ilmiah dapat menjadi salah satu strategi efektif dalam mengembangkan profesionalisme guru SD. Oleh karena itu, direkomendasikan agar kegiatan serupa dapat dilaksanakan secara rutin dan terus menerus untuk mendukung pengembangan profesionalisme guru dalam bidang penulisan karya ilmiah.